Визначення висоти переливної стінки двосекційного резервуара дощових стічних вод - Вовк, Леся (Видавництво Національного університету «Львівська політехніка», 2009)
In the article are described the design features twosektsional the storm-water storage tanks. Different approaches to determining the height of the overflow wall of the twosektsional storage tanks are analyzed. Depends of dimensionless parameters the height of the overflow wall are completly analytical studied. Are obtained a new formula for calculating the height of overflow chamber depended of the dimensionless coefficients of the ratio of areas of overflow chamber and storm-water storage tanks k and changes pressure discharge b.
Keywords: резервуар; РДСВ; storm-water storage tanks; adjusting volume; overflow wall